AB0448 Use of denosumab in patients with systemic lupus erythematosus: a real life multi-centric experience. (15th June 2017) - Crisafulli, F; Fredi, M; Bortoluzzi, A; Cavazzana, I; Furini, F; Govoni, M; Tincani, A; Franceschini, F
Abstract : Background: The occurrence of osteoporosis (OP) and fragility fractures (FF) is a frequent comorbidity in patients with systemic lupus erythematosus (SLE), mainly due to the concomitant presence of many risks factors for secondary osteoporosis (drugs, gender, concomitant diseases). The use of corticosteroids (CS) increases the risk of osteoporosis induced by corticosteroid (GIOP) and FF [1]. Denosumab is monoclonal antibody that binds to RANKL, inhibiting osteoclast formation and activation, used for both male and women OP to prevent FFx [2, 3]. Previous RCT [2] reported a numerically higher serious adverse events of infections in the denosumab users. In particular severe skin infections were significantly more frequent [4]. The possible increase in infection risk might be a concern in subjects treated with CS. The use of denosumab in SLE with GIOP patients is recently reported in 17 cases within a RCT [5]. Anyway, no data regarding the tolerability and disease activity during therapy were reported Objectives: Our aim was to analyze the prevalence, the tolerability, and relevant changes in disease activity or damage in a cohort of SLE patients treated with denosumab Methods: among all SLE patients currently followed in two referral Center we selected the ones that received at least one dose of denosumab. Clinical, serological manifestations, concomitant diseases and therapies were collected from clinical charts. Damage index (SDI), activity index (SLEDAI-2K) were calculated when denosumab was introduced (first cycle) and at the last evaluation (last cycle). For statistical analysis Chi-squared test or Fisher exact test was used Results: Among 793 patients in our cohorts, 21 (2.6%) were treated with denosumab. Demographic data reported a female prevalence (19 cases, 90%), mean age at onset of 38±12years, mean duration of disease of 28±10years and mean follow-up of 21±7.8years; most frequent manifestations were arthritis (90%), cutaneous (67%) and neurological (67%). All patients were still treated with CS (mean duration of 25±6.8 years) with a daily dose of 8.5±3.5mg/day. Other risk factors for OP were present in the majority of them: drugs (anticoagulants in 6pts, cyclosporin in 3 and antiepileptic in 2), chronic kidney disease (CKD) (4pts), hypovitaminosis D (15pts), anorexia, celiac disease and hemochromatosis (1pt, each). Indication for denosumab was OP with FFx in 17 cases: denosumab was used for a new FF during biphosphonates or after teriparatide. In the other 4 the indication was primary prevention with contraindications at the use of biphosphonates for concomitant severe CKD. Mean duration therapy was 4 cycles (range 1–8): data regarding disease activity, damage and adverse events are reported in table 1 . No new FFx developed in any of the included patients at the last evaluation available. Conclusions: In our cohorts denosumab is still used in few selected patients. However it could be considered as a valid option in GIOP patients because it was globally well tolerated and in our cohort it's efficacy in the prevention of new fragility fractures was confirmed References: Gudbjornsson, et al. Ann Rheum Dis 2002;61, 32–36. Cummings SR et al. N Eng J Med 2009; 61:756–65. Austin M et al. J Bone Miner Res 2012;27:687–93. Watts NB, Osteoporos Int 2012;23:327–37. Mok CC, et al. Bone 2015;75:222–8. Disclosure of Interest: None declared